PENGARUH MINYAK DAN GAS TERHADAP KINERJA PERTUMBUHAN EKONOMI REGIONAL: SEBUAH KUTUKAN ATAU ANUGERAH? - Ahmad Fahriza; Djoni Hartono (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
Natural resources, particularly oil and gas, are great benefit to the region that owns it and become one of the region's revenue sources. Nevertheless, Sachs and Warner (1995) found a phenomenon of natural resource curse indicating that the wealth of natural resources could hamper the economic growth. This research tries to see the existence of natural resource curse phenomenon in Indonesia through the performance of regional economic growth; and observes the differences of oil and gas contribution in the economic structure as an indicator of natural resource wealth in the area. Gross Regional Domestic Product Growth (PDRB) per capita without oil and gas is an indicator of the economic growth to see if the oil and gas are inhibiting or accelerating the growth of other sectors in the region's economy. Using data from 33 provinces in Indonesia within the period of 2006-2013, this study found a positive relationship between oil and gas contribution and per capita GDP growth without oil and gas. Based on these findings, natural oil and gas resources have become a boon to the province that owns them.